2011
DOI: 10.1002/psc.1415
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid and sialyl‐lactose glyco‐conjugates: design, synthesis and binding assays to lectins and swine influenza H1N1 virus

Abstract: The terminal parts of the influenza hemagglutinin (HA) receptors α2,6- and α2,3-sialyllactoses were conjugated to an artificial carrier, named sequential oligopeptide carrier (SOC(4) ), to formulate human and avian receptor mimics, respectively. SOC(4) , formed by the tripeptide unit Lys-Aib-Gly, adopts a rigid helicoids-type conformation, which enables the conjugation of biomolecules to the Lys-N(ε) H(2) groups. By doing so, it preserves their initial conformations and functionalities of the epitopes. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It has been concluded that HMO at or below the level found in breast milk increases innate immunity to respiratory viruses in vitro and can affect innate immunity. As a result of blocking hemagglutination of influenza viruses, immobilized 3 SL and 6 SL attachments prevent infectivity of influenza viruses [60,61]. A number of external HMO connections have been identified that bind to influenza virus [60,61].…”
Section: Respiratory Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been concluded that HMO at or below the level found in breast milk increases innate immunity to respiratory viruses in vitro and can affect innate immunity. As a result of blocking hemagglutination of influenza viruses, immobilized 3 SL and 6 SL attachments prevent infectivity of influenza viruses [60,61]. A number of external HMO connections have been identified that bind to influenza virus [60,61].…”
Section: Respiratory Virusesmentioning
confidence: 99%
“…As a result of blocking hemagglutination of influenza viruses, immobilized 3 SL and 6 SL attachments prevent infectivity of influenza viruses [60,61]. A number of external HMO connections have been identified that bind to influenza virus [60,61]. A number of additional sialic acids containing HMO that bind to influenza virus have also been identified.…”
Section: Respiratory Virusesmentioning
confidence: 99%
“…Immobilized 3′SL and 6′SL haven been shown to prevent infectivity of influenza viruses as a result of blocking the haemagglutins of influenza viruses ( 112 , 113 ), and Yu et al identified a number of additional sialic acid containing HMOs that bind to influenza virus ( 114 ). The effects of these HMOs was confirmed in a functional infection assay in vitro , where 6′SL and LNnT were shown to reduce the viral load of influenza in airway epithelial cells, and 2′FL did the same for respiratory syncytial virus (RSV) ( 92 ).…”
Section: Effects Of Hmos On Immune Function and Infection In mentioning
confidence: 99%
“…In addition to preventing the gut virus, HMOs also can inhibit respiratory virus infections [ 161 ]. 2′-FL has been shown to reduce viral load of respiratory syncytial virus [ 162 ].…”
Section: Effects Of Hmo On Infant Gut Microbiotamentioning
confidence: 99%